Factors affecting women’s well-being during the experience of acute myocardial infarction: a literature review - Foà, Chiara; Fuochi, Giulia; Fruggeri, Laura (Acta Biomedica Atenei Parmensis, 2015)
Background and aim of the work. Many factors influence the experience of acute myocardial infarction (AMI) and the well-being of affected patients; gender differences emerge in the patterns of influence, and women’s specificity is frequently highlighted. The purpose of this literature review is exploring in depth the experience of AMI in women. Methods. We selected and analyzed 44 articles on five factors strongly affecting women’s well-being after AMI: the delay in seeking treatment for symptoms, medical treatment, therapeutic adherence, social support and coping strategies. Results. The studies have attributed gender differences in the delay in seeking care for symptoms partly to a lack of information, but especially to socially built factors, such as the stereotypic belief of cardiac diseases as “male diseases”. Studies on the medical treatment show that women are less likely to undergo diagnostic tests and clinical treatment compared to men, but women’s older age may counterbalance the gender effect. Compared to men, therapeutic adherence appears lower in women, who find lifestyle changes more difficult to achieve; however, women rely more on social support, affecting positively their well-being. Also, women use more emotion-focused, evasive or fatalistic coping strategies; they are likely to minimize the severity of symptoms, to try to control the disease and to protect the significant others from the negative consequences of the infarction. Conclusions. Most studies highlight gender differences in the experience of AMI and in the patterns of influence of the factors we analyzed.